Perceptions of the Use of Project Based-Learning in the EFL Context - Atikah, Dewi; Syukri, Suhartini; Marhalisa, Marhalisa; Halim, Abdul; Abidin, Azwar (KnE Social Sciences, 2022)
The goal of this study was to determine the views of students about project-based learning (PBL) in an EFL setting. This was a descriptive qualitative study with 31 participants who filled out a questionnaire. The findings revealed that students had a positive impression of the PBL method and agreed that it should be used in the learning process. Furthermore, the PBL had benefits for students’ learning. Based on these findings, language teachers and teacher educators can use PBL as a teaching method to improve students’ perception and performance in the learning process. Keywords: English language learning, perception, project-based learning